Indonesia's Energy Diplomacy Strategy in Acquiring Oil Field in Algeria in 2013 - Cynthia Eka Wahyuni (Department of International Relations Universitas Pertamina, 2020)
Indonesia's energy diplomacy to Algeria was one of the efforts of the Indonesian government to maintain national energy security. Considering that the production produced from domestic sources has not been able to meet national energy needs, the Indonesian government tried to find exploration and production fields outside of Indonesia's territory. In effort to find fields that can be explored, the Indonesian government took a certain approach of diplomacy and negotiation with other governments. For that reason, this article aims to raise this topic is to find out what kind of strategy or approach was being carried out by the Indonesian government in conducting energy diplomacy in Algeria. To examine this topic, researcher used the concept of a grand strategy related to energy, energy diplomacy, and the concept of Indonesia's normative power. Researcher tried to prove that Indonesia's energy diplomacy strategy in acquiring oil fields in Algeria was done through strategy and decision making, which in the strategy there was a political approach and in the decision-making there was a business approach. The two approaches should synergize and complement each other, therefore consolidation between the two approaches was needed. Researchers using qualitative methods with analytical techniques using process tracing. One of the conclusions of this research is that the role of the Indonesian government was needed in supporting the acquisition of oil fields in Algeria.